Feel the fear - Child, Lauren (Child, Lauren. Ruby Redfort (Series), 2018)
Ruby Redfort is a thirteen-year-old undercover agent, code cracker, and all-around genius. But when Ruby sets out to stop a ghostly thief, she may have met her match, and her dare devil ways could get her killed.